Prognostic value of survivin in patients with non-small cell lung carcinoma: a systematic review with meta-analysis. - Lou Qian Zhang; Jun Wang; Feng Jiang; Lin Xu; Fu Yin Liu; Rong Yin (PLoS ONE)
Purpose The potential prognostic value of survivin in resected non-small cell lung carcinoma (NSCLC) is variably reported. The objective of this study was to conduct a systematic review of literatures evaluating survivin expression in resected NSCLC as a prognostic indicator. Methods Relevant literatures were identified using PubMed, EMBASE and Chinese Biomedicine Databases. We present the results of a meta-analysis of the association between survivin expression and overall survival (OS) in NSCLC patients. Studies were pooled and summary hazard ratios (HR) were calculated. Subgroup analyses and publication bias were also conducted. Results We performed a final analysis of 2703 patients from 28 evaluable studies. Combined HRs suggested that survivin overexpression had an unfavorable impact on NSCLC patients' survival with no evidence of any significant publication bias (HR = 2.03, 95%CI: 1.78-2.33, Egger's test, P = 0.24) and no severe heterogeneity between studies (I²  =  26.9%). Its effect also appeared significant when stratified according to the studies categorized by histological type, HR estimate, patient race, cutoff point (5%, 10%), detection methods and literature written language except for disease stage. Survivin was identified as a prognostic marker of advanced-stage NSCLC (HR = 1.93, 95%CI: 1.49-2.51), but not early-stage NSCLC (HR = 1.97, 95%CI: 0.76-5.14), in spite of the combined data being relatively small. Conclusion This study shows that survivin expression appears to be a pejorative prognostic factor in terms of overall survival in surgically treated NSCLC. Large prospective studies are now needed to confirm the clinical utility of survivin as an independent prognostic marker.